Papers of William James Linton - Linton, W. J. (William James), 1812-1897. (Yale University Photographic Services, 1839)
Letters and manuscripts.
Associated material held at National Library of Australia at mfm G 3906-3907 and MS 1698.
Positive also available.
Microfilm copy of original held in the Yale University Library, New Haven, Conn.
William James Linton was an English-born republican, Chartist, poet, publisher and printer.
Keywords: Linton, W. J. -- 1812-1897 -- Archives; Authors, English -- 19th century -- Archives